Essential Oil Composition and Lipoxygenase Activity of Irvingia malayana (SCOPUS) - Wan Mohd Nuzul Hakimi Wan Salleh (Tanjung Malim, 2021)
Essential Oil Composition and Lipoxygenase Activity of Irvingia malayana (SCOPUS) by Wan Mohd Nuzul Hakimi Wan Salleh